An Evaluation of the Impact of Pandemic Driven Lockdown on the Phytoplankton Biomass Over the North Indian Ocean Using Observations and Model - Seelanki, Vivek; Pant, Vimlesh (Frontiers in Marine Science, 2021)
The unprecedented nation-wide lockdown due to the ‘Coronavirus Disease 2019’ (COVID-19) affected humans and the environment in different ways. It provides an opportunity to examine the effect of reduced transportation and other anthropogenic activities on the environment. In the current study, the impact of lockdown on chlorophyll-a (Chl-a), an index of primary productivity, over the north Indian Ocean is investigated using observations and a physical-biogeochemical model. The statistics of model validation against observations shows a correlation coefficient of 0.85 (0.89), index of agreement as 0.90 (0.91), and root mean square error of 0.45°C (0.50 °C) for sea surface temperature (SST) over the Bay of Bengal (Arabian Sea). The model results are analysed to understand the upper-oceanic physical and biological processes during the lockdown. A comparison of the observed and model simulated data during the lockdown period (March-June, 2020) and pre-pandemic period (March-June, 2019) shows significant differences in the physical (temperature and salinity) and biogeochemical (Chl-a concentration, nutrient concentration and dissolved oxygen) parameters over the western Arabian Sea, western Bay of Bengal and regions off Sri Lanka. During the pandemic period, the reduced anthropogenic activities lead to a decrease in Chl-a in the coastal regions of western Arabian Sea and Bay of Bengal. The enhanced aerosol/dust transport due to stronger westerly winds enhanced phytoplankton biomass in the western Arabian Sea in May-June of the pandemic period.